Effect online game addiction in study grades among university students - Aslina Baharum; Afdhal Shaffy Sabili; Howard Benedict; Muhamad Ariff Asyraf Abu Nazril; Muhammad Nur Zubair Dzil Razman; Rahmad Zada Ahmad Khan; Farhana Diana Deris (European Journal of Molecular & Clinical Medicine, 2020)
This study is about the effect of playing various types of video games on the Universiti Malaysia Sabah students include Universiti Malaysia Sabah (UMS) Kota Kinabalu, Sandakan, and Labuan. This study used a quantitative method with 180 respondents with a few variables such as hours spend, changes of daily routine, types of games, and the changes in their grade. To collect the data sample, this study used online forms to create surveys for the UMS students to answer all the questions provided based on their experience in either video, computer, or mobile games. The data reported that respondents spent more than four hours a week playing video games in which they spent more than half an hour each day playing video games. The data also reported that most students spent more than four hours a week to study. This means for each hour they played the reprimand themselves by studying or for each hour they studied, they rewarded themselves by playing video games. Any which is remarkable as most students can score a 3.00 and higher for their current CGPA even they are playing video games every day. Following this study, we determined that there are no negative effects of gaming and changes in a daily routine on the student's study grades, but it has been shown that games do have effects on the student’s grades throughout the semester. From all the existing studies on this field, the impact of video games on the grades of the students cannot be ignored.